Review: Vaccine Myth-Buster – Cleaning Up With Prejudices and Dangerous Misinformation - Löffler, Paul (Frontiers in Immunology, 2021)
Although vaccines have already saved and will continue to save millions of lives, they are under attack. Vaccine safety is the main target of criticism. The rapid distribution of false information, or even conspiracy theories on the internet has tremendously favored vaccine hesitancy. The World Health Organization (WHO) named vaccine hesitancy one of the top ten threats to global health in 2019. Parents and patients have several concerns about vaccine safety, of which the ubiquitous anxieties include inactivating agents, adjuvants, preservatives, or new technologies such as genetic vaccines. In general, increasing doubts concerning side effects have been observed, which may lead to an increasing mistrust of scientific results and thus, the scientific method. Hence, this review targets five topics concerning vaccines and reviews current scientific publications in order to summarize the available information refuting conspiracy theories and myths about vaccination. The topics have been selected based on the author’s personal perception of the most frequently occurring safety controversies: the inactivation agent formaldehyde, the adjuvant aluminum, the preservative mercury, the mistakenly-drawn correlation between vaccines and autism and genetic vaccines. The scientific literature shows that vaccine safety is constantly studied. Furthermore, the literature does not support the allegations that vaccines may cause a serious threat to general human life. The author suggests that more researchers explaining their research ideas, methods and results publicly could strengthen the general confidence in science. In general, vaccines present one of the safest and most cost-effective medications and none of the targeted topics raised serious health concerns.